EFEKTIVITAS PENGGUNAAN MUSIK KLASIK DAN WARNA SECARA BERSAMAAN TERHADAP SHORT TERM MEMORY - Rahmi, Kartika Aulia; Rahmawati, Gustina; Hati, Bulan Permata; Bulut, Sefa; Rahmi, Tuti; Febriani, Utari (Jurnal Psikologi Terapan, 2023)
This study aimed to investigate the combined effects of classical music and color on short-term memory performance. A sample of 20 university students as participants was randomly assigned to experimental and control groups. Levene's Test was employed to assess the equality of variances between the groups, yielding a non-significant p-value (0.072 > 0.05), suggesting equal variances. Subsequently, a t-test assuming equal variances showed a non-significant result (p = 0.127 > 0.05). This implies no significant difference in short-term memory performance between the experimental and control groups. The findings contrast with prior research demonstrating the potential of classical music and color to enhance memory. While music's influence on cognition is established, this study suggests that their combined effects might not significantly enhance short-term memory. However, further research is recommended to explore various factors influencing this interaction and its potential applications in education and cognitive therapy. The research findings can serve as a foundation for students to comprehend that not all methods or stimuli will significantly enhance memory performance. Hence, students can become more discerning in selecting learning strategies that align with their preferences and cognitive traits.